(untitled) (Revista Cientifica Ingenio Magno, 2022)
Abstract— Electrocoagulation is a technology widely used in wastewater treatment to remove several pollutants like grease, metals, and organic molecules. This paper presents the result of exhaustive studies of electrocoagulation techniques applied to phenols removal, studying different control parameters such as pH, initial concentration of contaminants, electric current density, electrode types to establish their influence in the process efficiency. The different tests developed show phenol removals between 45,7% and 100% under optimum operating conditions. As a conclusion, the electric current density, the pH, the phenol concentration, the treatment time, the agitation, the material of the electrodes and the distance between them are parameters which affect directly the water treatment through electrocoagulation, nevertheless, the electric current density is the most determinant parameter in the system efficiency.